Quantifying and Adjusting Plasmon‐Driven Nano‐Localized Temperature Field around Gold Nanorods for Nucleic Acids Amplification. Issue 5 (8th April 2021) - You, Minli; Jia, Pengpeng; He, Xiaocong; Wang, Zheyu; Feng, Shangsheng; Ren, Yulin; Li, Zedong; Cao, Lei; Gao, Bin; Yao, Chunyan; Singamaneni, Srikanth; Xu, Feng
Abstract: Fast nucleic acid (NA) amplification has found widespread biomedical applications, where high thermocycling rate is the key. The plasmon‐driven nano‐localized thermocycling around the gold nanorods (AuNRs) is a promising alternative, as the significantly reduced reaction volume enables a rapid temperature response. However, quantifying and adjusting the nano‐localized temperature field remains challenging for now. Herein, a simple method is developed to quantify and adjust the nano‐localized temperature field around AuNRs by combining experimental measurement and numerical simulation. An indirect method to measure the surface temperature of AuNRs is first developed by utilizing the temperature‐dependent stability of Authiol bond. Meanwhile, the relationship of AuNRs′ surface temperature with the AuNRs concentration and laser intensity, is also studied. In combination with thermal diffusion simulation, the nano‐localized temperature field under the laser irradiation is obtained. The results show that the restricted reaction volume (≈aL level) enables ultrafast thermocycling rate (>10 4 °C s −1 ). At last, a duplex‐specific nuclease (DSN)‐mediated isothermal amplification is successfully demonstrated within the nano‐localized temperature field. It is envisioned that the developed method for quantifying and adjusting the nano‐localized temperature field around AuNRs is adaptive for various noble metal nanostructures and will facilitate the development of the biochemical reaction in the nano‐localized environment. Abstract : A simple method to quantify and adjust the nano‐localized temperature field around AuNRs is developed by combining experimental measurement and numerical simulation. The nano‐localized environment around AuNRs exhibits a great ability in achieving an ultrafast heating and cooling rate. As a proof‐of‐concept, the DSN‐mediated isothermal amplification is performed to verify the feasibility of plasmon‐driven nano‐localized nucleic acids amplification.